Fructose Promotes Crucian Carp Survival Against Aeromonas hydrophila Infection - Cao, Yunchao; Kou, Tianshun; Peng, Liaotian; Munang’andu, Hetron Mweemba; Peng, Bo (Frontiers in Immunology, 2022)
Aquatic food is becoming an important food source that provide micronutrients to human beings. The decline of wild aquatic animals make aquaculture become increasingly important to play this role. However, infectious diseases, especially bacterial infection, represent severe threat to aquaculture, which causes huge economic loss. Meanwhile, strategies in managing bacterial infection in an antibiotic-independent way is still lacking. In this study, we monitor the metabolomic shift of crucian carp upon Aeromonas hydrophila infection. We find that the metabolism of the fish died of infection is distinct from the ones survive. By multivariate analysis, we identify fructose as a crucial biomarker whose abundance is significantly different from the dying and survival group where the survival group has higher content of fructose than the dying group. Exogenous supplementation of fructose increases fish survival rate by 27.2%. Quantitative gene expression analysis demonstrated that fructose enhances the expression of lysozyme and complement 3 expression, which is also confirmed in the serum level. Furthermore, the augmented lysozyme and C3 level enhance serum cell lytic activity that contribute to the reduced bacterial load in vivo. Thus, our study demonstrates a metabolism-based approach to manage bacterial infection through modulating immune response to clear bacterial infection.